Socio-Economic Redistribution Practices in the Prophet's Birthday Tradition: An Islamic Economic Perspective: A Case Study of Akkor Village, Pamekasan - Miftahul Arifin; Uly Mabruroh Halida; Abdul Mukti Thabrani (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to comprehensively describe the practice of philanthropy in the tradition of celebrating the Prophet's birthday in Akkor Village, Pamekasan, and analyze community motivations and their compliance with Islamic economic principles. The research method uses a qualitative approach with an ethnographic study type. Data collection was carried out through participatory observation, in-depth interviews, and documentation, which were then analyzed using interactive methods. The results of the study indicate that philanthropy in the Prophet's birthday is manifested in the form of sèkor, tandhâ' arèk, provision of bherkat, self-help facilities, and donations in the form of labor. Community motivation is driven by religious awareness as a form of worship and Madurese cultural values ​​​​that uphold mutual cooperation and the value of brotherhood. The tradition of Maulid is not just a religious ritual, but a mechanism for inclusive social redistribution, strengthening community cohesion, and driving the local micro economy. This practice significantly contributes to a sustainable communal economic model. Substantively, all these activities are in line with Islamic economic principles such as infaq, almsgiving, tabrru', distributive justice ('adl), ukhuwwah, and ta'awun.